Symposium 6: Design in use - the case of two CoPs: ePreP and Did@cTIC - Van de Wiele, Nathalie; Rossier, Annick; Charlier, Bernadette (Proceedings of the International Conference on Networked Learning, 2008)
This paper aims to illustrate how the services developed within the PALETTE project (Pedagogically sustained Adaptive LEarning Through the exploitation of Tacit and Explicit knowledge - 2006-2009) can answer specific needs of different CoPs. Through the analysis of two cases (ePrep CoP and CoP Did@cTIC), the reader will discover how the involvement of CoPs in the project has had an impact on support for learning within CoPs (pedagogical interests, organizational). The article shows also how the involvement of CoPs in the project, through the Participatory Design Methodology, helped to develop technical services that are relevant to communities of practice (CoP). The ePrep case describes some Participatory Design Methodology (PDM) events, involving, in term of Design in use, ePrep CoP members and PALETTE researchers. ePrep CoP members are, for the most of them, teachers in "Classes préparatoires aux grandes écoles" (CPGE), a first higher education cycle preparing students for the competitive entrance exams to the French "Grandes Ecoles". Arisen in 2006 under the guidance of PALETTE researchers, the ePrep CoP conducts pedagogical projects for French and French-speaking CPGEs and similar establishments, using PALETTE tools. According to the PDM, a lot of Design in use events have been organised between CoP members and PALETTE researchers in order to provide the CoP with the tools and services ideally suited to its needs. These events are first presented in a chronological way, then their outcomes are analysed, on a technological point of view, and on a pedagogical point of view. For the technological point of view, we will see how Design in use makes the tools evolve. For the pedagogical point of view, we will see the impact of this evolution on the ePrep CoP members’ professional practices. We will conclude that Design in use is a fruitful way for developing tools and services for Communities of Practice, allowing both CoP members and technological researchers to increase their learning in their own filed. The « Centre de Didactique Universitaire » of the University of Fribourg in Switzerland offers continuous training in Higher Education and Technology. The aim of this training is to develop teaching and academic competences for the teaching profession. One part of this training is to give the possibility to the participants to solve problems of teaching practice through their participation in community of practices called CoP Did@cTIC. The Did@cTIC case highlights two main changes both to the CoPs practices and the PALETTE services infer from the PDM. The first one is the use of structured documents and the other one is the development of an effective information search.